Application of geophysical prospecting methods ERT and MASW in the landslide of Daofu County, China - Zhang, Gang; Tu, Fangzhou; Tang, Yushu; Chen, Xingchang; Xie, Kuilin; Dai, Sen (Frontiers in Earth Science, 2023)
Natural disasters such as debris flow caused by earthquakes seriously threaten the local infrastructure and economy, as well as the lives of people in the area. As the material source of debris flow, it has significance to accurately and effectively study the underground structure of the landslide to prevent debris flow disasters. A landslide has a complex structural system, and its underground characteristics play an important role in its stability. The early identification of fracture surfaces and unstable bodies, and assessment of potential hazards are essential for prevention and protection. The research object of this paper is a landslide that occurred in Yige Village, Xianshui Town, Daofu County, which is on the Xianshui River Earthquake Zone, an area subject to frequent earthquakes. In western Sichuan, the frequent occurrence of landslides has caused considerable economic losses. Developing methods for efficient and accurate risk assessment is a top priority. The Daofu landslide is a typical example of a landslide directly threatening the road below and forming a debris flow channel. The lithology is composed of Jurassic sedimentary rocks, such as marl and clay, covered by limestone. In this study, we combined traditional methods (drilling and field investigation) with two geophysical techniques, multichannel analysis of surface waves (MASW) and electrical resistivity tomography (ERT) to effectively determine the electrical characteristics, velocity characteristics and spatial structure of the landslide. It is found that the buried depth of the sliding surface of the landslide is about 16–20 m. The sliding body above the sliding surface forms a low velocity and low resistivity Quaternary cover. The rock mass below the sliding surface is Triassic Zhuwo Formation sandstone and slate with high velocity and high resistivity. According to comprehensive analysis, the landslide lacks sufficient stability under rainstorm. Our study shows that the use of MASW and ERT can quickly and effectively characterize the subsurface of landslides to assess landslide risk and prevent debris flow hazards.